State regulation of nuclear energy: features of legal regulation under martial law - Bytiak, O. Yu (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is devoted to the study of current aspects and features of the legal regulation of state regulation of nuclear energy in conditions of martial law. The primary importance and special relevance of the issues of restoring energy potential and ensuring the sustainable functioning of the energy complex of Ukraine, in which nuclear energy occupies an important place, were emphasized. It is emphasized that the main thing in optimizing the work of the nuclear complex and bringing it to the proper level of functioning is to improve the organizational and legal mechanism of state regulation of activities in the energy market, to determine effective legal means of such regulation, taking into account important features of the objects and the system of subjects of organizational and economic powers and the optimal model of interaction between them, considering the complex issues of the nuclear energy sector and the need to ensure effective centralized management. The norms of the Law of Ukraine «On the Use of Nuclear Energy and Radiation Safety» and the Regulations on the State Inspection of Nuclear Regulation of Ukraine were analyzed in the context of general aspects of building a system of state regulation of the use of nuclear energy. Some issues of improving and bringing the national legislation of Ukraine in the field of nuclear energy safety into line with the provisions of EU law were considered. It has been established that the main vector of state policy should be aimed at improving the norms of current legislation, taking into account the implementation of international legal obligations undertaken by Ukraine on the legal regulation of nuclear and radiation safety in Ukraine, which provide for the harmonization of current legislation with the EU acquis. A conclusion was made on the need to continue implementing measures to strengthen the independence of the nuclear energy sector, institutional stability and effectiveness of state regulation of nuclear energy safety. It was determined that in order to ensure the sustainable functioning and further development of nuclear energy, and the proper implementation of Ukraine’s international obligations in the field of nuclear energy, it is necessary to intensify the processes of improving the norms of current legislation and strategic planning.